2003
DOI: 10.1016/s0002-9440(10)63515-8
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Monoxide Inhalation Protects Rat Intestinal Grafts from Ischemia/Reperfusion Injury

Abstract: Carbon monoxide (CO), a byproduct of heme catalysis by heme oxygenases, has been shown to exert anti-inflammatory effects. This study examines the cytoprotective efficacy of inhaled CO during intestinal cold ischemia/reperfusion injury associated with small intestinal transplantation. Orthotopic syngenic intestinal transplantation was performed in Lewis rats after 6 hours of cold preservation in University of Wisconsin solution. Three groups were examined: normal untreated controls, control intestinal transpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
187
2
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(198 citation statements)
references
References 37 publications
8
187
2
1
Order By: Relevance
“…There have been several reports that inhalation of CO can be protective against acute rejection of intestine, lung, and kidney transplants (11,12,23,24). The protective actions of CO inhalation in transplantation are associated with a decrease in inflammation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been several reports that inhalation of CO can be protective against acute rejection of intestine, lung, and kidney transplants (11,12,23,24). The protective actions of CO inhalation in transplantation are associated with a decrease in inflammation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-inflammatory actions of CO inhalation are associated with a decrease in cytokines such as IL-6 and inducible nitric oxide synthase as well as an increase in the total antioxidant power (11). Because analogous mechanisms are believed to contribute to tissue injury after renal ischemia, it is possible that the CO released from transition metal carbonyls is able to Figure 6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Western blots were performed using anti-adenosine monophosphate-activated protein kinase (AMPK)-alpha rabbit monoclonal antibodies, anti-phosphorylated (pThr 172) AMPK-alpha (Cell Signaling, Boston, MA), rabbit monoclonal antibodies for anti-cleaved caspase-3 (Cell Signaling,) and mouse anti-human monclonal antibody for human ␤-actin (Sigma) [21].…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Hence, tissue viability increases because of improved nutritional supply and better elimination of toxic residues of oxidative stress. Recently, Nakao et al [30] demonstrated that inhalation of CO ameliorates IR injury in a model of bowel transplantation.…”
Section: Discussionmentioning
confidence: 99%